Monitoring Human Viral Pathogens Reveals Potential Hazard for Treated Wastewater Discharge or Reuse - Cuevas-Ferrando, Enric; Pérez-Cataluña, Alba; Falcó, Irene; Randazzo, Walter; Sánchez, Gloria (Frontiers in Microbiology, 2022)
Wastewater discharge to the environment or its reuse after sanitization poses a concern for public health given the risk of transmission of human viral diseases. However, estimating the viral infectivity along the wastewater cycle presents technical challenges and still remains underexplored. Recently, human-associated crAssphage has been investigated to serve as viral pathogen indicator to monitor faecal impacted water bodies, even though its assessment as biomarker for infectious enteric viruses has not been explored yet. To this end, the occurrence of potentially infectious norovirus genogroup I (GI), norovirus GII, hepatitis A virus (HAV), rotavirus A (RV) and human astrovirus (HAstV) along with crAssphage was investigated in influent and effluent water sampled in four wastewater treatment plants (WWTPs) over one year by a PMAxx-based capsid integrity RT-qPCR assay. Moreover, influent and effluent samples of a selected WWTP were additionally assayed by an in situ capture RT-qPCR assay (ISC-RT-qPCR) as estimate for viral infectivity in alternative to PMAxx-RT-qPCR. Overall, our results showed lower viral occurrence and concentration assessed by ISC-RT-qPCR than PMAxx-RT-qPCR. Occurrence of potentially infectious enteric virus was estimated by PMAxx-RT-qPCR as 88 to 94% in influent and 46 to 67% in effluent wastewaters with mean titers ranging from 4.77 to 5.89, and from 3.86 to 4.97 log10 GC/L, with the exception of HAV that was sporadically detected. All samples tested positive for crAssphage at concentration ranging from 7.41 to 9.99 log10 GC/L in influent and from 4.56 to 6.96 log10 GC/L in effluent wastewater, showing higher mean concentration than targeted enteric viruses. Data obtained by PMAxx-RT-qPCR showed that crAssphage strongly correlated with norovirus GII (ρ=0.67, p<0.05) and weakly with HAstV and RV (ρ=0.25-0.30, p<0.05) in influent samples. In effluent wastewater, weak (ρ=0.27-0.38, p<0.05) to moderate (ρ=0.47-0.48, p<0.05) correlations between crAssphage and targeted virus were observed. Overall, these results corroborate crAssphage as an indicator for faecal contamination in wastewater while a poor marker for either viral occurrence and viral integrity/infectivity. Despite the viral load reductions detected in effluent compared to influent wastewaters, the estimates of viral infectivity based on viability molecular methods might pose a concern for (re)-using of treated water.